2007
DOI: 10.1002/jor.20492
|View full text |Cite
|
Sign up to set email alerts
|

Coefficients of friction, lubricin, and cartilage damage in the anterior cruciate ligament‐deficient guinea pig knee

Abstract: The coefficient of friction (COF) of articular cartilage is thought to increase with osteoarthritis (OA) progression, and this increase may occur due to a decrease in lubricin concentration. The objectives of this study were to measure the COF of guinea pig tibiofemoral joints with different stages of OA and to establish relationships between COF, lubricin concentrations in synovial fluid, and degradation status using the Hartley guinea pig model. Both hind limbs from 24 animals were harvested: seven 3-month-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 27 publications
2
104
1
1
Order By: Relevance
“…The decrease in SF lubricin concentrations following ACL injury has been corroborated in animal models. In the guinea pig, transection of the ACL led to significantly reduced SF lubricin levels 9 months after surgery, and this corresponded to an increase in the coefficient of friction of the articulating surfaces (19). Following rabbit ACL and posterior cruciate ligament (PCL) transection, SF lubricin concentrations in lavage fluid progressively decreased and lubricin was undetectable on Western blots, and this appeared to be associated with increased cartilage damage (20).…”
Section: Effects Of Acl Injury On Sf Lubricin Concentrationsmentioning
confidence: 99%
“…The decrease in SF lubricin concentrations following ACL injury has been corroborated in animal models. In the guinea pig, transection of the ACL led to significantly reduced SF lubricin levels 9 months after surgery, and this corresponded to an increase in the coefficient of friction of the articulating surfaces (19). Following rabbit ACL and posterior cruciate ligament (PCL) transection, SF lubricin concentrations in lavage fluid progressively decreased and lubricin was undetectable on Western blots, and this appeared to be associated with increased cartilage damage (20).…”
Section: Effects Of Acl Injury On Sf Lubricin Concentrationsmentioning
confidence: 99%
“…RA patients varied with respect to lubricin expression, where the patients with low levels of lubricin had more aggressive joint disease (22). A relationship between the pathogenesis of OA and down-regulation of lubricin has been suggested in several animal models (23)(24)(25)(26). Furthermore, treatment of rat joints with injections of recombinant lubricin has indicated its protective effects on chondrocytes, suggesting the benefits of lubricating molecules as a possible therapy for OA (1,16).…”
Section: Lubricin (Or Proteoglycan 4 (Prg4)mentioning
confidence: 99%
“…Some studies have maintained conditions found within the joint to test the boundary lubricating ability of novel intra-articular treatments (Elsaid et al, 2005;Teeple et al, 2007Teeple et al, , 2008, although not SAPLs. There is even less information known about the properties of articular cartilage when the joint atmosphere is conserved and a joint viscous friction model used.…”
Section: Introductionmentioning
confidence: 99%